Regulation of splenic contraction persists as a vestigial trait in white‐blooded Antarctic fishes. Issue 1 (23rd October 2020) - Joyce, William; Axelsson, Michael
Abstract: In fishes, the spleen can function as an important reservoir for red blood cells (RBCs), which, following splenic contraction, may be released into the circulation to increase haematocrit during energy‐demanding activities. This trait is particularly pronounced in red‐blooded Antarctic fishes in which the spleen can sequester a large proportion of RBCs during rest, thereby reducing blood viscosity, which may serve as an adaptation to life in cold environments. In one species, Pagothenia borchgrevinki, it has previously been shown that splenic contraction primarily depends on cholinergic stimulation. The aim of the present study was to investigate the regulation of splenic contraction in five other Antarctic fish species, three red‐blooded notothenioids ( Dissostichus mawsoni Norman, 1937, Gobionotothen gibberifrons Lönnberg, 1905, Notothenia coriiceps Richardson 1844) and two white‐blooded "icefish" ( Chaenocephalus aceratus Lönnberg, 1906 and Champsocephalus gunnari Lönnberg, 1905), which lack haemoglobin and RBCs, but nevertheless possess a large spleen. In all species, splenic strips constricted in response to both cholinergic (carbachol) and adrenergic (adrenaline) agonists. Surprisingly, in the two species of icefish, the spleen responded with similar sensitivity to red‐blooded species, despite contraction being of little obvious benefit for releasing RBCs into the circulation. Although the icefish lineage lost functional haemoglobin before diversifying over the past 7.8–4.8 millions of years, they retain the capacity to contract the spleen, likely as a vestige inherited from their red‐blooded ancestors.